Compact tunable bandpass filter with wide tuning range of centre frequency and bandwidth using coupled lines and short‐ended stubs. Issue 8 (1st June 2016) - Zhu, He; Abbosh, Amin
Abstract : A tunable bandpass filter with wide tuning range of both its centre frequency and bandwidth is presented. This type of filter is a key element in modern wideband and multiband systems. The proposed filter is based on short sections of two pairs of shunt connected parallel‐coupled lines and short‐ended stub resonators, which are tuned using varactor diodes. The structure has two resonant modes as well as one‐side edge transmission zero that can be relocated and controlled for any desired position. A thorough theoretical analysis is utilised to find the initial values of the filter's design parameters and estimate its performance. To validate the proposed design and its theoretical analysis, two prototype filters are fabricated and tested. The measured results indicate wide tuning range ratios for the centre frequency and bandwidth of up to 2.85 (0.52 to 1.48 GHz) and up to 5.2 (55 to 285 MHz), respectively. The fabricated filters are compact with an overall size (in guided wavelengths at the centre frequency) of less than 0.06 × 0.16.